POLA PEMBINAAN ISLAM DI PESANTREN: Studi Kasus di Pondok Pesantren Baitul Anshor Cimahi - Setia Permana, Irfan (Jurnal El-Hamra : Kependidikan dan Kemasyarakatan, 2018)
Boarding School is a place that facilitates teenagers in religious formation, morality and noble morals, both for those whose parents are well off, or whose parents are not well-off, or whose parents are busy with their work. Baitul Anshor Boarding School is an institution that has a program in the development of religious, morality and noble character, that is with aspects of coaching ruhiyyah, fikriyah coaching and coaching jasadiyyah done for 24 hours from start the child wakes up until the child sleeps again. In this study the focus of attention is the form of guidance patterns of students or students who are developed in educating students in Boarding School. Data in this research is obtained from primary data and secondary data. Primary data are respondents. In this study the respondents are students or students of Baitul Anshor Boarding School. The informants, namely leaders of institutions, caregivers, and community leaders around Baitul Anshor Boarding School. The research approach used in this research is by qualitative method. While the data collection techniques used are by interview, observation and documentation. The pattern of guidance in Baitul Anshor Boarding School in providing guidance to students or santrinya takes place effectively and efficiently. The coaching of students or students of Baitul Anshor Boarding School can provide a new color in the development of Islamic education through coaching in accordance with the teachings of Islam is pure and in accordance with the demands of the times. This shows that Islamic educational institutions have an active role and have a high awareness of the needs of the community for quality education.Key Words: Coaching, Islam, Boarding